Analisis Faktor-faktor yang Mempengaruhi Permintaan Tenaga Listrik Konsumen Industri Besar PT Perusahaan Listrik Negara (Persero) - Aminullah Assagaf (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is analysis of electricity demand, and focus for large industry sector in PT Perusahaan listrik Negara (Persero) or PT PLN (Persero). Dependent variable is demand electricity or kWh sales, and independent variable consist of install capacity, average tariff, and rate of capacity using percustomers. Step of research and process result based on SPSS calculation, and use cross section data on January 2010. Obtain result that install capacity and rate of capacity using percustomers has given positif impact, and average tariff has given negative impact. Install capacity and rate of capacity using percustomers variable has significant influence to electricity demand of large industry sector, but average tariff variable has not significant influence to electricity demand of large industry sector. PLN’s management has to observe growth of explanatory variable to make policy for demand and supply equilibrium and toward customers satisfaction.Keywords: Electricity demand: Strategy Management, and Microeconomic